Investigation of the predictors of the response to Iguratimod therapy: A post-hoc analysis of post-marketing surveillance study. Issue 4 (3rd July 2020) - Ishiguro, Naoki; Shibata, Kai; Yoshimura, Akiko; Ikeuchi, Satoshi; Ishii, Mika
Abstract: Objectives: The treatment response according to patient disease activity during Iguratimod therapy for rheumatoid arthritis has not been sufficiently assessed. A post-hoc analysis of post-marketing surveillance was performed. The treatment effect was evaluated using the European League against Rheumatism (EULAR) response criteria. Methods: Disease Activity Score (DAS) 28 was assessed at various time points. Patients showing a moderate or good response according to the EULAR response criteria at 24 weeks after the start of Iguratimod therapy were considered Responders. Propensity score matching was also performed, after which the factors with the greatest effect on the treatment evaluation were investigated. Results: The mean DAS28 at the start of administration and after 24 weeks was 4.31 and 2.52, respectively, in the Responder and 3.48 and 3.48, respectively, in the Non-responder. After propensity score matching for patient characteristics, the primary factors found to be related to being a Responder were concomitant use of methotrexate (MTX) with Iguratimod, and prior treatment with MTX before the start of Iguratimod. Conclusion: As factors related to the treatment effect, the concomitant use of MTX may contribute to achieving a better effect, and this study has shown that real-world are consistent with the results of clinical trials.